Very Low Ventricular Pacing Rates Can Be Achieved Safely in a Heterogeneous Pacemaker Population and Provide Clinical Benefits: The CANadian Multi-Centre Randomised Study-Spontaneous AtrioVEntricular Conduction pReservation (CAN-SAVE R) Trial - Thibault, Bernard (J Am Heart Assoc, 2015)
BACKGROUND: It is well recognized that right ventricular apical pacing can have deleterious effects on ventricular function. We performed a head-to-head comparison of the SafeR pacing algorithm versus DDD pacing with a long atrioventricular delay in a heterogeneous population of patients with dual-chamber pacemakers. METHODS AND RESULTS: In a multicenter prospective double-blinded randomized trial conducted at 10 centers in Canada, 373 patients, age 71±11 years, with indications for dual chamber DC pacemakers were randomized 1:1 to SafeR or DDD pacing with a long atrioventricular delay (250 ms). The primary objective was twofold: (1) reduction in the proportion of ventricular paced beats at 1 year; and (2) impact on atrial fibrillation burden at 3 years, defined as the ratio between cumulative duration of mode-switches divided by follow-up time. Statistical significance of both co-primary end points was required for the trial to be considered positive. At 1 year of follow-up, the median proportion of ventricular-paced beats was 4.0% with DDD versus 0% with SafeR (P<0.001). At 3 years of follow-up, the atrial fibrillation burden was not significantly reduced with SafeR versus DDD (median 0.00%, interquartile range [0.00% to 0.23%] versus median 0.01%, interquartile range [0.00% to 0.44%], respectively, P=0.178]), despite a persistent reduction in the median proportion of ventricular-paced beats (10% with DDD compared to 0% with SafeR). CONCLUSIONS: A ventricular-paced rate <1% was safely achieved with SafeR in a population with a wide spectrum of indications for dual-chamber pacing. However, the lower percentage of ventricular pacing did not translate into a significant reduction in atrial fibrillation burden. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov/ Unique identifier: NCT01219621.